Erosion-driven uplift in the Gamburtsev Subglacial Mountains of East Antarctica - Paxman, G; Watts, A; Ferraccioli, F; Jordan, T; Bell, R; Jamieson, S; Finn, C (Elsevier, 2016)
The relative roles of climate and tectonics in mountain building have been widely debated. Central to this debate is the process of flexural uplift in response to valley incision. Here we quantify this process in the Gamburtsev Subglacial Mountains, a paradoxical tectonic feature in cratonic East Antarctica. Previous studies indicate that rifting and strike-slip tectonics may have provided a key trigger for the initial uplift of the Gamburtsevs, but the contribution of more recent valley incision remains to be quantified. Inverse spectral (free-air admittance and Bouguer coherence) methods indicate that, unusually for continents, the coherence between free-air gravity anomalies and bedrock topography is high (>0.5) and that the elastic thickness of the lithosphere is anomalously low (<15 km), in contrast to previously reported values of up to ∼70 km. The isostatic effects of two different styles of erosion are quantified: dendritic fluvial incision overprinted by Alpine-style glacial erosion in the Gamburtsevs and outlet glacier-type selective linear erosion in the Lambert Rift, part of the East Antarctic Rift System. 3D flexural models indicate that valley incision has contributed ca. 500 m of peak uplift in the Gamburtsevs and up to 1.2 km in the Lambert Rift, which is consistent with the present-day elevation of Oligocene–Miocene glaciomarine sediments. Overall, we find that 17–25% of Gamburtsev peak uplift can be explained by erosional unloading. These relatively low values are typical of temperate mountain ranges, suggesting that most of the valley incision in the Gamburtsevs occurred prior to widespread glaciation at 34 Ma. The pre-incision topography of the Gamburtsevs lies at 2–2.5 km above sea-level, confirming that they were a key inception point for the development of the East Antarctic Ice Sheet. Tectonic and/or dynamic processes were therefore responsible for ca. 80% of the elevation of the modern Gamburtsev Subglacial Mountains. ©